The concept of discipline - White, E (2013)
Discipline was an enduring concept in the works of John Milton (1608-1674), yet its meaning shifted over the course of his career: initially he held that it denoted ecclesiastical order, but gradually he turned to representing it as self-willed pious action. My thesis examines this transformation by analysing Milton’s complex engagement in two distinct periods: the 1640s and the 1660s-70s. In Of Reformation (1641), Milton echoed popular contemporary demands for a reformation of church discipline, but also asserted through radical literary experimentation that poetry could discipline the nation too (Chapter 1). Reflecting his dislike for intolerant Presbyterians in Parliament and the Westminster Assembly, the two versions of The Doctrine and Discipline of Divorce (1643 and 1644) reconsider discipline as a moral imperative for all men, rooted in domestic liberty (Chapter 2). Although written long after this period, the long poetry that Milton composed after the Restoration reveals his continued interrogation of the concept. The invocations of the term ‘discipline’ by Milton’s angels in Paradise Lost (1667) sought to encourage dissenting readers to faithfulness and co-operation (Chapter 3). Paradise Regained and Samson Agonistes (1671) advance the concept in the language of ‘piety,’ emphasising that ‘pious hearts’ are the precondition for godly action in opposition to contemporary Anglican ‘holy living’ (Chapter 4). In analysing Milton’s shifting concept of discipline, my thesis contributes to scholarship by showing his sensitivity to contemporary mainstream religious ideas, outlining the Christian—as opposed to republican or Stoic—notions of praxis that informed his ethics, and emphasising the disciplinary aspect of his doctrinal thought. Overall, it holds that in discipline, as word and concept, Milton expressed his faith in the capacity of writing to change its reader, morally and spiritually.